Pengaruh Pembiayaan Murabahah Dan Pendampingan Usaha (Bank Tabungan Pensiunan Nasional) BTPN Syariah Terhadap Perkembangan UMKM Di Kecamatan Sukatani Kabupaten Bekasi - Setiani, Indah; Shafariah, Hanuna (JAMBIS : Jurnal Administrasi Bisnis, 2025)
The purpose of this study was to examine the impact of Murabaha Financing and Business Assistance provided by BTPN Syariah on the development of MSMEs in Sukatani Subdistrict, Bekasi Regency. A quantitative research methodology with a descriptive approach was used, where data were gathered through questionnaires distributed to 97 MSME customers of BTPN Syariah. Data analysis was conducted using multiple linear regression with IBM SPSS version 27. The findings showed that Murabaha Financing (X1) has a positive and significant effect on MSME Development (Y) by 72.4%. Business Assistance (X2) also had a positive and significant impact on MSME Development (Y) by 71.1%. When combined, Murabaha Financing (X1) and Business Assistance (X2) account for 78.0% of the positive and significant influence on MSME Development (Y) in Sukatani Subdistrict, with the remaining 22% being attributed to other factors not explored in this study.